2000
DOI: 10.1007/s002610000036
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative pneumoperitoneum as detected by CT: prevalence, duration, and relevant factors affecting its possible significance

Abstract: Pneumoperitoneum is a common phenomenon after abdominal surgery, decreasing in frequency with time. The air is most often residual and not a sign of disruption of the gastrointestinal tract. Obesity, female sex, and occurrence of free air several weeks after surgery are factors suggestive of a leak, but the significance of a postoperative pneumoperitoneum on CT should be determined mainly by the clinical setting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
47
2

Year Published

2002
2002
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(59 citation statements)
references
References 0 publications
10
47
2
Order By: Relevance
“…Positive pressure ventilation may lead to the introduction of air into the abdominal cavity by direct passage through microscopic diaphragmatic defects or through the media- laparoscopic approach, the currently preferred gas used for insufflation is carbon dioxide, which is much more rapidly absorbed than room air entering the peritoneal cavity in laparotomy, and thus the pneumoperitoneum after laparoscopic procedures is smaller and of shorter duration. (14,15) (45,46) Occasionally in some cases, the underlying aetiology of the non-surgical pneumoperitoneum is never found and the condition is described as idiopathic. (47,48) How to distinguish surgical and non-surgical pneumoperitoneum…”
Section: Definition and Aetiologymentioning
confidence: 99%
See 1 more Smart Citation
“…Positive pressure ventilation may lead to the introduction of air into the abdominal cavity by direct passage through microscopic diaphragmatic defects or through the media- laparoscopic approach, the currently preferred gas used for insufflation is carbon dioxide, which is much more rapidly absorbed than room air entering the peritoneal cavity in laparotomy, and thus the pneumoperitoneum after laparoscopic procedures is smaller and of shorter duration. (14,15) (45,46) Occasionally in some cases, the underlying aetiology of the non-surgical pneumoperitoneum is never found and the condition is described as idiopathic. (47,48) How to distinguish surgical and non-surgical pneumoperitoneum…”
Section: Definition and Aetiologymentioning
confidence: 99%
“…(5)(6)(7)(8)(10)(11)(12)(13)(14)17,(19)(20)(21)(22)(23)(26)(27)(28)(29)(30)(31)(32)(33)(34)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46)(47)(48)(49)(50) It is mainly due to the lack of knowledge of the attending physicians which leads to unnecessary laparotomy with possible morbidity. (6) When we acknowledge the possibility of non-surgical pneumoperitoneum, the primary goal is to discern surgical from non-surgical pneumoperitoneum.…”
Section: Definition and Aetiologymentioning
confidence: 99%
“…Bevan [6]presented a patient with a 15-day duration of postoperative PP, this being the longest in the series, whereas Harrison et al [7]reported the duration of postoperative PP as 23 days after gastrectomies, and pointed out that the type of the abdominal surgery influenced the duration of postoperative PP, upper abdominal surgeries, particularly gastrectomies having the longest one. Gayer et al [8]presented a series of 89 patients who underwent 92 abdominal operations, in which 18 days was the longest period of time until the free air disappeared. They found that free air was significantly more often present in men and asthenic patients, but they could not demonstrate an effect of age and the type of the procedure on the duration of postoperative PP.…”
Section: Discussionmentioning
confidence: 99%
“…An up-right chest X-ray is the simplest and cheapest diagnostic tool to detect intra-abdominal free air, whereas CT scan of the abdomen is the most sensitive diagnostic test and may be helpful to detect very small amounts of free air if clinically indicated. The type and the duration of operation, the length of the incision, the initial amount of air introduced during surgery, presence of adhesions, drains, and stomas, age, gender and BMI of the patients are among the many proposed contributing factors to the duration of postoperative PP [5, 6, 7, 8, 10, 11]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation